LIPUS-S/B@NPs regulates the release of SDF-1 and BMP-2 to promote stem cell recruitment-osteogenesis for periodontal bone regeneration - Yan, Shujin; Wang, Dong; Zhang, Liang; Gan, Tian; Yao, Huan; Zhu, Hui; He, Yiman; Yang, Ke (Frontiers in Bioengineering and Biotechnology, 2023)
Poly (lactic-co-glycolic acid)-based nanoparticles (PLGA NPs) have been widely used as the carrier for sustainable drug delivery. However, the drug release from the NPs was usually incomplete and uncontrollable. Herein, a low intensity pulsed ultrasound (LIPUS) assisted SDF-1/BMP-2@nanoparticles (S/B@NPs) system was fabricated to facilitate stem cell recruitment-osteogenesis for periodontal bone regeneration.In this work, S/B@NPs were prepared with double-emulsion synthesis method. Then the S/B release profile from NPs was evaluated with or without LIPUS treatment. Afterwards, the stem cell recruiting and osteoinductive capacities of LIPUS-S/B@NPs were detected with human periodontal ligament cells (hPDLCs) in vitro and in a rat periodontal bone defect model.The results indicated that S/B@NPs were successfully prepared and LIPUS could effectively regulate the release of S/B and increase their final releasing amount. Moreover, LIPUS-S/B@NPs system This is a provisional file, not the final typeset article significantly promoted hPDLCs migrating and osteogenesis in vitro and recruiting rBMSCs to the rat periodontal defect and facilitated bone regeneration in vivo.Our LIPUS assisted S/B@NPs system can effectively facilitate stem cell recruitment and periodontal bone regeneration. Considering its reliable safety and therapeutic effect on bone fracture, LIPUS, as an adjuvant therapy, holds great potential in the regulation of drug delivery systems for bone healing.